(untitled) (Journal of Information Technology and Digital World, 2025)
The increasing elderly population calls for creative approaches to healthcare. To improve elderly patients with chronic conditions health outcomes, optimize resource utilization, and provide more individualized care, this study proposes an AI-driven framework that integrates Social Determinants of Health (SDOH), Electronic Health Records (EHRs), Multi-Omics Data, and Resource Optimization Models. This strategy fixes systemic inefficiencies and guarantees scalable, affordable, and equitable geriatric care by utilizing AI. With 94% accuracy, 95% F1 score, and 92% scalability, the suggested model outperforms conventional techniques. By addressing gaps in the use of clinical and non-clinical data and enhancing the management of chronic diseases, this integration transforms geriatric healthcare.